Isma'ili Modern : Globalization and Identity in a Muslim Community - Steinberg, Jonah (Book collections on Project MUSE., 2011)
This title explores how Isma'ili Muslims, a major sect of Shi'i Islam, form a community that is intriguing in its deterritorialized social organization.